Analisis Kompetensi Pedagogik Guru Dalam Proses Pembelajaran di SD Muhammadiyah 16 Surakarta - Wardani, Winda Kusuma, Drs. Saring Marsudi, SH. M.Pd (2017)
The aim of this research is to examine : 1) the comprehension level of Teacher pedagogical competence in SD Muhammadiyah 16 Surakarta. 2) Implementation of teacher pedagogical competence in the learning process in SD Muhammadiyah 16 Surakarta . 3) what the problems encountered of teacher in the learning process in SD Muhammadiyah Surakarta 16. 4) Solution that must fight by teachers in learning process in SD Muhammadiyah 16 Surakarta. The kind of this research is qualitative research with the design of the case study research. The informant of this research are the headmaseter, the teacher four, five, and six class. Data collection techniques used in this research are interviews, observation, and documents. Data were analyzed through the steps of data collection, presentation, data reduction, and conclusion. Investigation technique of data validity is done by triangulation techniques and triangulation of sources. The result of research showedcomprehenssion pedagogical competence of teachers involved of the characteristics of learners, syllabus and lesson plans, evaluation and assessment, learning theory, students' academic compprehenssion in learning. The iImplementation of pedagogical competence in the learning process are observations and students approache, develop syllabi and make the learning device at the beginning of the school year, using the strategy of group discussions, peer tutoring, environmental approach in learning, using LCD and laptop, the learners follow extracurricular in school, make an assessment in written tests, oral tests, action tests, and portofolios. Problem in the learning process are boisterous students, lack of concentration and lack of understanding on the subject matter. The solutions for those problem are teacher must resolute to students, giving punisment, and conduct guidance. this research can be conclude that teachers have to understand the pedagogic competence in the learning process in SD Muhammadiyah 16 Surakarta .